Mobile treatment for epileptic seizures using little scale electronic sensors - Devi Majety, Vasumathi; Murali, G (International Journal of Engineering and Technology, 2018)
Epilepsy-Abnormal behaviors (neuro disorder) of a patient.The epileptic seizure patient need an ongoing frame work. It must support in acute cases. The brilliant epilepsy recognition and ready framework is a propelled innovation by which an electronic device is introduced. Utilizing that pack, the life of the individual who is truly affecting with the condition can be anticipated. As per World Health Organization (WHO), epilepsy is a standout amongst the most well-known essential sicknesses of the focal sensory system around the world [1], which is exasperated by the sudden variable that portrays the event of an epileptic occasion. In this manner, the capacity to recognize scene preceding its beginning is introduced as a relief variable to the upsetting effects that emerge from this situation [2]. The casing will be tolerable, confirms the condition and also alerts by a SMS to the the specialist in question for the life of the patient. To realize all the above plan, mainly utilized four modules: scaled down scale controller, KEIL module, ARDUINO module and GSM module.